Effect of Feed Restriction on Carcass Yield and Meat Quality Characteristics of Broiler Chicken - Sikder, S. K.; Majumder, S. C.; Das, S. K.; Chatterjee, J. K. (International Journal of Bio-resource and Stress Management, 2012)
Ninety six unsexed three weeks old Vencob strain broiler chicks were randomly allocated to four experimental treatments. Each group included three replicates of eight chicks. Chicks in the first group (T1) were fed ad libitum while those in the second (T2), third (T3) and fourth (T4) groups were fasted 4, 6 and 8 h day-1, respectively during experimental period, i.e. 4-6 weeks of age in a completely randomized design to evaluate the effect on growth performance, meat quality and proximate composition of broiler chicken. During the first three weeks of age, chicks were fed ad libitum a commercial starter diet with 21.94% crude protein (CP) and 2,785 KCal kg-1 metabolizable energy (ME), however, from 4 to 6 weeks of age, chicks were fed a commercial grower diet with 19.43% CP and 2,874 KCal kg-1 ME. The result revealed that feed deprivation for 4, 6 or 8 h day-1 decreased body weight of broiler chicks compared to those fed ad libitum at the end of the experiment. Feed restriction had significant effect on dressing percentage, primal cut-up-parts and relative weights of giblets (gizzard, heart and liver) and small intestine among the experimental birds. Insignificant difference was observed among the treatments in neck and wings weight gain. The pH of the thigh and breast meat of control group was significantly higher than treatment groups. However, among the different treatment groups, insignificant value was observed in water holding capacity. T3 group of broiler showed lowest fiber diameter but highest tenderness scores. In respect to proximate composition, breast and thigh meat from feed-deprived groups exhibited most desirable characteristics in terms of lower fat and higher protein contents.